Screening Mammalian Cochlear Hair Cells to Identify Critical Processes in Aminoglycoside-Mediated Damage - Lim, Hyun Woo; Pak, Kwang; Ryan, Allen F.; Kurabi, Arwa (Frontiers in Cellular Neuroscience, 2018)
There is considerable interest in discovering drugs with the potential to protect inner ear hair cells (HCs) from damage. One means of discovery is to screen compound libraries. Excellent screening protocols have been developed employing cell lines derived from the cochlea and zebrafish larvae. However, these do not address the differentiated mammalian hair cell. We have developed a screening method employing micro-explants of the mammalian organ of Corti to identify compounds with the ability to influence aminoglycoside-induced HC loss. The assay is based on short segments of the neonatal mouse organ of Corti, containing ~80 HCs which selectively express green fluorescent protein (GFP). This allows the screening of hundreds of potential protectants in an assay that includes both inner and outer HCs. This review describes various screening methods, including the micro-explant assay. In addition, two micro-explant screening studies in which antioxidant and kinase inhibitor libraries were evaluated are reviewed. The results from these screens are related to current models of HC damage and protection.